IMPLEMENTASI PEMBELAJARAN BERBASIS GAME EDUKASI QUIZIZZ PADA MATA PELAJARAN PKN UNTUK MENINGKATKAN KARAKTER RASA INGIN TAHU SISWA DI MADRASAH IBTIDAIYAH - Burhanudin Afandi; Nany Kholilah; Wahyu Trisnawati; Husni Mubarok (https://journal.metanusantara.com/pedagogia, 2026)
Citizenship Education (PKn) learning in Islamic Elementary Schools (Madrasah Ibtidaiyah) still faces challenges in the form of low student participation and curiosity due to the dominance of teacher-centered learning methods. This situation indicates the need for learning innovations that can create more interactive learning experiences and encourage active student involvement. One possible alternative is educational game-based learning through the Quizizz application. This study aims to describe the implementation of Quizizz educational game-based learning in Civics and analyze its contribution to improving students' curiosity in Islamic Elementary Schools (Madrasah Ibtidaiyah). This study used a qualitative approach with a field research design. The study was conducted at an Islamic Elementary School in Cepu District during the 2025/2026 academic year. The study participants consisted of two fourth-grade Civics teachers, Mr. Abdul Rohim, S.Pd. and Ms. Eva Nur Izza, S.Pd., who were selected using a purposive sampling technique. Data were collected through semi-structured interviews, observation, and documentation. They were then analyzed using the Miles, Huberman, and Saldaña interactive analysis model, which included data condensation, data presentation, and conclusion drawing. The results of the study indicate that the implementation of Quizizz was carried out through the planning, implementation, and evaluation stages of learning, integrated with Civics learning objectives. The use of Quizizz has been shown to increase student engagement, learning motivation, and curiosity, demonstrated by increased questioning, seeking additional information, discussion participation, and enthusiasm during learning. Furthermore, Quizizz helped teachers conduct more effective learning evaluations. Thus, Quizizz can be an innovative learning medium that supports character building and improves the quality of Civics learning in Islamic Elementary Schools.